BACTERIA EATING POLLUTION AND GENERATING ELECTRICITY - DHARMESH HARWANI (International Journal of Pharma and Bio Sciences, 2013)
The continuous use of fuels like petroleum is recognized as unsustainable because of their natural exhaustion and contribution to the pollution in the environment. Not only for the environmental perspective but also for the economic sustainability, we necessarily need to develop alternative, renewable and pollution free fuels. Harvesting energy from the sun (solar energy), earth (geothermal energy), water (hydropower), or wind are few of the alternative and renewable energy sources. It has been well appreciated that fuels, such as ethanol, butanol, methane and hydrogen can be produced by microorganisms. But by using bacteria in a microbial fuel cell (MFC), electricity can be extracted from wastewater, converting organic material in the waste water to electricity using bacteria, leaving behind clean drinking water in the process (bacteria are appreciated as electricigens). Harvesting electricity with microbial fuel cells can proficiently convert organic wastes, renewable biomass and even mud into electricity and harmless by-products. This capability offers the potential for using bacteria (or their components) to generate electricity at low cost while transforming industrial, domestic, and farm toxic pollution. This is an exciting aspect for human kind around the world who lacks adequate sanitation and resources to clean up toxic waste. Though the MFC technology is not yet well developed to produce substantial quantities of energy in a cost effective way, the area reviewed in the present communication requires more research and is highly prospective.